Zambia Poverty Assessment : Stagnant Poverty and Inequality in a Natural Resource-Based Economy - World Bank (Washington, DC, 2014)
As in many countries throughout Sub-Saharan Africa and around the developing world, poverty in Zambia is overwhelmingly a rural phenomenon. In 2010 the moderate poverty rate in rural areas was 74 percent, more than double the urban poverty rate of 35 percent. The economic growth continued throughout the decade, reaching an impressive annual average of 5.7 percent, and by 2011 the World Bank recognized Zambia as a middle-income country. Rising incomes have been densely concentrated among a relatively small segment of the urban workforce, while extremely high urban unemployment rates effectively block the rural labor force from participating in the country's more dynamic economic sectors, a phenomenon that is discussed in detail in this analysis. The principal challenge faced by Zambian policymakers and the international donor community will be to extend the returns to growth throughout the country and especially to the rural poor. Marginal improvements in economic and social indicators can be accomplished through targeted interventions in the rural economy, but enduring, structural income growth and the widespread reduction of poverty will only be achievable through broad-based employment creation in the urban industrial and service sectors. This report is organized as follows: chapter one discusses poverty and inequality; chapter two gives poverty profile; chapter three discusses labor market, employment, and wages; and chapter four focuses on poverty and social spending.